2008
DOI: 10.1111/j.1742-4658.2008.06314.x
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of GSK837149A, an inhibitor of human fatty acid synthase targeting the β‐ketoacyl reductase reaction

Abstract: GSK837149A has been identified as a selective inhibitor of human fatty acid synthase (FAS). The compound was first isolated as a minor impurity in a sample found to be active against the enzyme in a high‐throughput screening campaign. The structure of this compound was confirmed by NMR and MS studies, and evaluation of the newly synthesized molecule confirmed its activity against FAS. The compound and other analogs synthesized, all being symmetrical structures containing a bisulfonamide urea, act by inhibiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…The dibenzenesulfonamide urea GSK837149A was identified as a low, nanomolar FASN inhibitor by high-throughput screening at GlaxoSmithKline. Biochemical studies showed that GSK837149A is a reversible inhibitor of the FASN β-ketoacyl reductase domain, but its poor cell permeability prevented the study of its mechanism in cells [78]. A systematic screening of 250,000 natural product extracts led to the isolation of platensimycin as a potent inhibitor of bacterial FabF/B with a broad-spectrum Gram-positive antibacterial activity [79].…”
Section: Fasn As a Potential Drug Target In Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…The dibenzenesulfonamide urea GSK837149A was identified as a low, nanomolar FASN inhibitor by high-throughput screening at GlaxoSmithKline. Biochemical studies showed that GSK837149A is a reversible inhibitor of the FASN β-ketoacyl reductase domain, but its poor cell permeability prevented the study of its mechanism in cells [78]. A systematic screening of 250,000 natural product extracts led to the isolation of platensimycin as a potent inhibitor of bacterial FabF/B with a broad-spectrum Gram-positive antibacterial activity [79].…”
Section: Fasn As a Potential Drug Target In Cancer Therapymentioning
confidence: 99%
“…Their study can be hampered by their lack of potency, selectivity or cell permeability [48,59,65,78]. FASN inhibition initiates selective apoptosis of cancer cells both in vivo and in vitro , which may involve accumulation of toxic intermediary metabolite malonyl-CoA with reduction of both membrane synthesis and phospholipid function leading to both cytostatic and cytotoxic effects [23,80].…”
Section: Mechanism Of Action Of Fasn Inhibitorsmentioning
confidence: 99%
“…The mammalian KR has received some attention as a potential anti-cancer target, and compounds have been identified as selective inhibitors. 144 …”
Section: -Ketoacyl Acp Reductase (Kr)mentioning
confidence: 99%
“…Ursolic acid, a pentacyclic triterpenoid acid, as well as the tea polyphenols, epigallo-catechin gallate (EGCG) and epicatechin gallate, interact with the KR domain of FASN, thereby inhibiting its activity [73, 74]. Recently, GSK837149A was also serendipitously identified as a potent and selective inhibitor of the KR domain [75]. Unfortunately, this compound and subsequent analogs exhibit poor cellular permeability.…”
Section: Using 11c-acetate Pet To Predict Response To Therapies That mentioning
confidence: 99%